Effect of the Addition of Carboxymethyl Cellulose and Virgin Coconut Oil On Physicochemical And Sensory Mellorine Honey Mango Peel - Aulia Aretha Rachma Putri Frisandi; Rosida (AJARCDE (Asian Journal of Applied Research for Community Development and Empowerment), 2026)
Mellorine is a frozen dessert similar to ice cream that uses vegetable oil as a substitute for milk fat. This study utilized honey mango peel as a raw material for mellorine production. The research aimed to determine the effect of carboxymethyl cellulose (CMC) and virgin coconut oil (VCO) addition on the physicochemical and sensory characteristics of honey mango peel mellorine, as well as to determine the best treatment combination that produces mellorine with desirable physicochemical quality and consumer acceptance. This study employed a quantitative method using a Completely Randomized Design (CRD) with a two-factor factorial arrangement and two replications. The first factor was CMC concentration (0.4%, 0.7%, and 1%), while the second factor was VCO concentration (5%, 7.5%, and 10%). The observed parameters included fat content, crude fiber, overrun, melting rate, total soluble solids, viscosity, emulsion stability, antioxidant activity, vitamin C, and sensory properties. The results showed that CMC had no significant effect on fat content, while VCO significantly affected fat content. Both CMC and VCO had no significant effect on crude fiber content. However, the addition of CMC and VCO significantly affected overrun, melting rate, total soluble solids, viscosity, and emulsion stability. In sensory evaluation, only texture showed a significant effect, whereas color, aroma, and taste were not significantly different among treatments. The best treatment was obtained from the addition of 1% CMC and 10% VCO, producing mellorine with good overrun, slower melting rate, smooth texture, and acceptable sensory characteristics. The product also contained high antioxidant activity and vitamin C. These findings indicate that the combination of CMC and VCO improved the physicochemical stability and consumer acceptance of honey mango peel mellorine. Contribution to Sustainable Development Goals (SDGs):SDG 2: Zero Hunger SDG 3: Good Health and Well-Being SDG 12: Responsible Consumption and Production